Application Analysis of the Cost Accounting Model for Micro Entities in Profit Optimization Efforts - Tantular Rachman, Yoga; Indah Bayunitri, Bunga; Surayya Mohd Saudi, Nur (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze the application of cost accounting in micro, small, and medium enterprises in optimizing profits as a means of small industries so that they can maintain their business sustainability. The research method used by researchers is the descriptive method. Data from direct observations and interviews are processed and described based on sources from the literature (articles, books, magazines, etc.). The results of this study are a model of calculating sales and cost of goods sold for products produced by these small businesses. Furthermore, the results of this study are expected to provide an illustration for the small business in determining the selling price more accurately in order to get an optimal profit.